Natural Killer Cells in Anti-Neutrophil Cytoplasmic Antibody-Associated Vasculitis - A Review of the Literature - Fuchs, Sina; Scheffschick, Andrea; Gunnarsson, Iva; Brauner, Hanna (Frontiers in Immunology, 2022)
Anti-neutrophil cytoplasmic antibody (ANCA)- associated vasculitis (AAV) is a group of systemic autoimmune diseases characterized by inflammation of small- and medium-sized vessels. The three main types of AAV are granulomatosis with polyangiitis (GPA), microscopic polyangiitis (MPA) and eosinophilic granulomatosis with polyangiitis (EGPA). A growing number of studies focus on natural killer (NK) cells in AAV. NK cells are innate lymphoid cells with important roles in anti-viral and anti-tumor defense, but their roles in the pathogenesis of autoimmunity is less well established. In this review, we will present a summary of what is known about the number, phenotype and function of NK cells in patients with AAV. We review the literature on NK cells in the circulation of AAV patients, studies on tissue resident NK cells and how the treatment affects NK cells.